Adipose tissue characteristics as a new prognosis marker of patients with locally advanced head and neck cancer - Carrilho, Larissa Ariel Oliveira; Juliani, Fabiana Lascala; Moreira, Rafaella Caroline de Lellis; Dias Guerra, Livia; Santos, Fernanda Silva; Padilha, Daniela Morais de Holanda; Branbilla, Sandra Regina; Horita, Vivian Naomi; Novaes, Davi Magalhães Leite; Antunes-Correa, Lígia Macedo; Lima, Carmem Silvia Passos; Mendes, Maria Carolina Santos; et al. (Frontiers in Nutrition, 2025)
BackgroundPatients with head and neck cancer (HNC) are at increased risk of malnutrition due to the presence of tumor and treatments. Body composition is a prognostic factor in these patients. However, the relationship between adipose tissue characteristics and survival in HNC is still unclear.ObjectiveTo evaluate the associations of adiposity, the radiodensity of adipose tissue and muscularity with the prognosis of patients with locally advanced HNC undergoing to chemoradiotherapy.MethodsThis retrospective study included 132 patients diagnosed with locally advanced HNC. Body composition assessment was performed using computed tomography (CT) images at the level of the third cervical vertebra (C3). The total adipose tissue radiodensity (TATR), the total adipose tissue index (TATI) and skeletal muscle index (SMI) were evaluated. The primary outcome was overall survival (OS).ResultsPatients in the highest TATI tertile had a lower risk of mortality when compared to those in the lowest tertile, HR: 0.56, 95% confidence Interval (CI): 0.32–0.96; p = 0.039. The highest TATR tertile was not associated with death. Patients with greater adiposity had a higher median survival compared to patients with medium and lower TATI (p = 0.0193). Individuals with lower TATI had lower energy intake than patients with higher TATI (p = 0.03). Additionally, patients with low muscularity had worse OS in the multivariable analysis (HR: 1.77, 95% CI: 1.01–3.07; p = 0.044).ConclusionIn patients with locally advanced HNC, our findings underscore the significance of elevated adiposity, beyond maintained muscularity, as independent protective factors for overall survival. Our study highlights the critical importance of assessing body composition and initiating early nutritional interventions to improve the prognosis of these patients.